Survive Factors Influencing on Tendency of Internal Auditors for Whistle - blowing in Iran - Ghasem Blue (بررسی‌های حسابداری و حسابرسی, 2021)
Objective: Wrongdoing consumes a lot of resources in years and harms companies in many ways. Based on other developed countries experiences, improving and developing whistle blowing is one of the effective and best ways of preventing and detecting wrongdoing activities. The whistle blowing describes the action of a worker disclosing (internally or externally) questionable practices, from within an organization, to the parties that can take remedial actions. Internal auditors are the best people that could do this job and the result show itself as silence, leaving the company and reporting. Recent studies show that the rate and role of internal auditors in detecting, and whistle blowing is increased. However, professional entities in the world are not engaged in this topic and their opinion is not clear about the responsibilities and role of internal auditors in whistle blowing concept. Whistle-blowing describes the action of a worker disclosing questionable practices, from within an organization, to the parties that can take remedial actions. Few researches conducted in the world about whistle blowing and internal audits. This is the first study that examined Iranian internal auditors’ tendency toward the whistle blowing.Methods: This research is applied in terms of purpose, and terms of method is among quasi-experimental research and in the field of behavioral research. The purpose of this study is to identify factors that influence internal auditors in Iran to blow the whistle. Six individual-level, independent variables (attitude, injunctive norm, descriptive norm, perceived behavioral control, self-efficacy and awareness of the whistle-blowing protection legislation) are examined for their relationship with the dependent variable (intention to blow the whistle). Moral intensity is examined for its moderating effect on the relationships that exist between the seven independent variables and the dependent variable. In this research we used Scenario-based survey and using Structural Equation and analyses 458 questionnaires for internal auditors between 2019 and 2020 is examined using PLS software.Results: Results of this study show that there is a significant and strong relation between descriptive norms, self-efficiency, whistle-blowing protection legislation and weak significant relation between attitude, injunctive norms and tendency of internal auditors for the whistle blowing. Also, age, gender, education, employment position, work experience and auditing work experience as moderating variables have a significant relation with internal auditors for the whistle blowing. Finally, results show that moral intensity is a moderator in the research model and affects significantly the relationship between research variables. Finally, a conceptual framework for the tendency of internal auditors to report whistle blowing was developed and presented.Conclusion: In order to achieve the positive consequences of whistle blowing and increase the effectiveness of the internal audit, it is necessary to consider the factors affecting the tendency to whistle blowing be considered by decision makers, policy makers and stakeholders, and provide the basis for strengthening its infrastructure and developing a culture of reporting erroneous actions. On the other hand, due to the importance and impact of knowledge of internal auditors about their role, responsibility for Whistle blowing, recommended that professional institutions and set standards for reporting wrongdoing and whistle blowing by internal auditors and increase the awareness of internal auditors.